1984
DOI: 10.1159/000194690
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sulfur Hexafluoride, SF<sub>6</sub>, in the Management of the Postpneumonectomy Pleural Space

Abstract: After a pneumonectomy in patients of advanced age with lung cancer, over-inflation of the contralateral lung causes a further emphysematous change. This aggravation of emphysematous disturbances occasionally leads to serious cardiopulmonary dysfunctions. Therefore, we have devised a new therapeutic method which consists in injecting sulfur hexafluoride, SF6, an inert gas, into the postpneumonectomy pleural space so as to maintain the chest cavity. As SFó gas is slowly absorbed through the pleura, ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In our model, although we reduced the tidal volume after PNX, we observed prominent inflation of the right lung, protrusion of the diaphragmatic lobe into the left pleural cavity, and a left-shift of the mediastinum in the PNX group at the time of sacrifice, similar to that observed clinically in residual lungs after PNX [43]. Overinflation of the residual lung after PNX may cause lung tissue injury with release of HMGB1 into the alveolar space [41].…”
Section: Discussionsupporting
confidence: 76%
“…In our model, although we reduced the tidal volume after PNX, we observed prominent inflation of the right lung, protrusion of the diaphragmatic lobe into the left pleural cavity, and a left-shift of the mediastinum in the PNX group at the time of sacrifice, similar to that observed clinically in residual lungs after PNX [43]. Overinflation of the residual lung after PNX may cause lung tissue injury with release of HMGB1 into the alveolar space [41].…”
Section: Discussionsupporting
confidence: 76%
“…In this case, we employed SF 6 gas, which is a readily available and straightforward procedure. SF 6 exhibits twofold expansion within 72–92 h post-injection, subsequently returning to the injected volume within a week [ 10 ]. Kimura reported that this patient complained of chest discomfort 3 days after the injection [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have no way of prediction for this syndrome and attempts of preventing this natural space obliteration process have largely been abandoned [4]. We do know that together with displacement of mediastinal structures, hyperinflation of the contralateral lung becomes possible and is beneficial in terms of pulmonary function tests and quality of life in long term follow up of pneumonectomy patients [5].…”
Section: Discussionmentioning
confidence: 99%